2008
DOI: 10.1007/s10643-008-0246-3
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Language in Early Childhood Settings: What Really Counts?

Abstract: Previous research indicates that, prior to entering kindergarten, most children are exposed to some type of formal or direct mathematics instruction. However, the type of mathematical language and the frequency of its use vary greatly in terms of its emphasis on academic content. This study investigated the types and frequency of mathematical language used in six classrooms for children ranging in age from birth to five years. The study site was a quality early childhood setting at a state university in Southw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 5 publications
1
41
0
8
Order By: Relevance
“…Moreover, qualitative studies show preschool teachers use little mathematics language in their classrooms and introduce few structured mathematics activities (Rudd et al 2008;Schoenfeld and Stipek 2011;Young-Loveridge et al 1998). Tablet computers may be an effective tool to help early educators deliver consistent and high-quality mathematics instruction (Blackwell 2014;Zomer and Kay 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, qualitative studies show preschool teachers use little mathematics language in their classrooms and introduce few structured mathematics activities (Rudd et al 2008;Schoenfeld and Stipek 2011;Young-Loveridge et al 1998). Tablet computers may be an effective tool to help early educators deliver consistent and high-quality mathematics instruction (Blackwell 2014;Zomer and Kay 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers also must guide them in doing so. Students who needed remedial mathematics instruction required more connection between life language and formal mathematical language It showed that mathematical schema and representation decided the comprehension of mathematical language in problem solving [26]. The transformation to reform mathematics teaching was a daunting task because teachers needed to realize what such a classroom would really look like [11].…”
Section: Mathematical Language Was Also Addressed In the Principles Amentioning
confidence: 99%
“…In addition, it is highly likely that children do not have enough opportunities to discuss the critical attributes of the shapes due to limited exposure to the geometric shapes in various sizes and orientation. According to several studies (e.g., (KLIBANOFF et al, 2006;RUDD et al, 2008) suggests, better classroom lessons about geometric shapes would improve preschool children's understanding of the square.…”
Section: Implications For Practicementioning
confidence: 99%